The Alberta Infant Motor Scale: A tool for the assessment of motor aspects of neurodevelopment in infancy and early childhood - Eliks, Małgorzata; Gajewska, Ewa (Frontiers in Neurology, 2022)
According to the recommendations of the American Academy of Pediatrics, the surveillance of motor development should accompany systematic appointments with medical professionals in infancy and early childhood. One of the standardized tools for evaluating motor development is the Alberta Infant Motor Scale (AIMS). This paper aims to present assumptions and psychometric properties of the AIMS, the methodology of assessment of an infant's performance with the AIMS, and research on the validation and standardization of the AIMS as well as the use of the scale as an outcome measure. We conducted a non-systematic literature review using three electronic databases: PubMed, Scopus, and Embase (from June 1992 to February 2022). We included original research with a full-text manuscript in English. No geographical restrictions were applied. The search terms “alberta infant motor scale” AND “reliability” OR “validity” and “alberta infant motor scale” AND “norms” OR “reference” OR “standardization” were used for literature review on the validation and standardization of the AIMS in other non-Canadian populations. This narrative review also focuses on how the AIMS is applied as an outcome measure in research by presenting studies on the AIMS conducted over the last decade. Our review found that the AIMS is widely used for both research and clinical purposes. The AIMS has been used as an outcome measure in both interventional and observational studies conducted on both neurotypical infants and those with conditions affecting motor development. The advantages of the scale are its infant-friendliness, time duration of the examination, and relative ease of application for an examiner. The scale has been validated and standardized in many countries.